A new feather mite of the genus Pteronyssoides Hull, 1931 (Astigmata: Pteronyssidae) from thrushes (Passeriformes: Turdidae) in the New World - Mironov, Sergey V.; Hernandes, Fabio A. [UNESP]; Valim, Michel P. (Springer, 2016)
A new feather mite species, Pteronyssoides turdinus n. sp. (Acariformes: Pteronyssidae), is described from two species of thrushes, Turdus amaurochalinus Cabanis (type-host) and T. leucomelas Vieillot (Passeriformes: Turdidae) in Minas Gerais, Brazil. The new species belongs to the parinus species group and most clearly differs from previously known species of this group by the following features: in both sexes of P. turdinus, setae c2 are anterior to the level of the sejugal furrow; in males, the anterior margin of the hysteronotal shield has a deep trapezoidal concavity, setae d1 are situated on the striated tegument, the adanal shield is represented by a narrow longitudinal sclerite, and tarsus and tibia of legs IV are subequal in length; in females, the opisthosomal sclerites are split into proper opisthosomal sclerites and pygidial fragments encompassing the bases of setae h2 and h3. This is the first description of a feather mite of the genus Pteronyssoides Hull, 1931 from birds of the family Turdidae.